Unjust Enrichment and Public Law - Williams, R (Taylor and Francis, 2015)
The recent explosion of litigation concerning unjust enrichment and public authorities, in particular HMRC, has presented important challenges to both public and private law, as well as for the relationship between domestic and EU law. If we are to understand and decide these cases properly we must do so from a hybrid perspective which takes account of both the key aspects of the claims: public and private. Doing so will clarify the law and help to prevent further complex and costly litigation.